Mathematical modelling of the mass-spring-damper system - A fractional calculus approach - Gómez Aguilar, José Francisco; Rosales García, Juan; Bernal Alvarado, Jesus; Guía, Manuel (Acta Universitaria, 2012)
In this paper the fractional differential equation for the mass-spring-damper system in terms of the fractional time derivatives of the Caputo type is considered. In order to be consistent with the physical equation, a new parameter is introduced. This parameter characterizes the existence of fractional components in the system. A relation between the fractional order time derivative and the new parameter is found. Different particular cases are analyzed